2011
DOI: 10.1083/jcb.201102142
|View full text |Cite
|
Sign up to set email alerts
|

Energy determinants GAPDH and NDPK act as genetic modifiers for hepatocyte inclusion formation

Abstract: Differential expression and activity of the cellular energy regulators GAPDH and NDPK underlie reactive oxygen species–induced damage in the mouse liver and may contribute to human liver disease progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
43
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 59 publications
3
43
0
Order By: Relevance
“…These models of GAPDH aggregation are supported by the observation that insoluble disulfide-cross-linked forms of GAPDH have been found in vivo (11)(12)(13)18). Our data suggest that cysteine oxidation contributes to GAPDH aggregation; however, we found that oxidation of non-cysteine residues has a more influential and primary role in GAPDH aggregation.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…These models of GAPDH aggregation are supported by the observation that insoluble disulfide-cross-linked forms of GAPDH have been found in vivo (11)(12)(13)18). Our data suggest that cysteine oxidation contributes to GAPDH aggregation; however, we found that oxidation of non-cysteine residues has a more influential and primary role in GAPDH aggregation.…”
Section: Discussionsupporting
confidence: 54%
“…For instance, insoluble aggregates of GAPDH have been observed in the affected tissues of patients with Alzheimer disease (13) and alcoholic liver cirrhosis (12). Interestingly, GAPDH is also a susceptibility locus for late onset Alzheimer disease (21).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…To determine if ␤-catenin knockdown exacerbates oxidative injury in vivo, we subjected KD mice and littermates to a DDC-containing diet for 3 weeks. DDC is a porphyrinogenic agent that causes chronic oxidative liver damage and Mallory-Denk body formations (39). Effective ␤-catenin deletion in response to doxycycline withdrawal for 4 weeks was confirmed by mRNA and protein analysis ( Fig.…”
Section: ␤-Catenin Signaling Provides Hepatocyte Protection Against Omentioning
confidence: 98%